Zakat, Belanja Pemerintah, Utang Pemerintah, Dan Pertumbuhan Ekonomi Indonesia: Sebuah Analisis Kritis Melalui Literature Review - M. Rif'an Syadali (ITB AAS INDONESIA Surakarta, 2023)
In the current era of globalization, economic growth is one of the main indicators in assessing the quality and development of a country. The purpose of this study is to examine more deeply the role of zakat, government spending, government debt, and Indonesia's economic growth with a research method using a literature review. The results of this study indicate that zakat, government spending, and government debt have an important role in Indonesia's economic growth. Strong synergy between the government, society, and the private sector in optimizing zakat potential and managing government spending and debt will create inclusive and sustainable economic growth in Indonesia. Through a critical literature review analysis, this research is expected to significantly contribute to science and public policy relevant to the Indonesian government and society to maintain and increase significant economic growth in the future.